PENGARUH LITERASI DIGITAL TERHADAP PRESTASI AKADEMIK EKONOMI DENGAN PEMBELAJARAN INFORMAL DIGITAL SEBAGAI VARIABEL MEDIASI - Putri, Septy Aliyana; Prakoso, Albrian Fiky (Edunomic : Jurnal Ilmiah Pendidikan Ekonomi Fakultas Keguruan dan Ilmu Pendidikan, 2024)
Economic academic achievement has not reached the good category during learning activities due to a lack of digital literacy, especially data and information literacy. The aim of this research is to analyze the influence of digital literacy on economic academic achievement with digital informal learning as a mediating variable. This research uses a quantitative approach with Partial Least Squares Structural Equation modeling (PLS-SEM) analysis assisted by WarpPLS 8.0 software. Data was collected by census techniques and obtained from 236 students in class X and XI at SMA Muhammadiyah 10 GKB Gresik. The results of the research showed that digital literacy has a positive and significant correlation with digital informal learning and their economic academic achievement. In addition, digital informal learning as a mediating variable has a positive and significant influence on the relationship between digital literacy and economic academic achievement. This could be novelty in this research because the mediating role of digital informal learning between digital literacy and economic academic achievement remains unexplored. For this reason, it is recommended that educational institutions and students consider digital literacy and digital informal learning to improve their economic academic achievement. Keywords: Digital Literacy, Digital Informal Learning, Economic Academic Achievement, Data and Information Literacy